Implementation of Foot Massage Therapy on Hemodynamic Status Stability in Acute Myocardial Infarction (AMI) Patients in Intensive Cardiovascular Care Unit (ICVCU) of Dr. Moewardi Hospital Surakarta - Wulandari, Novita Kurnia; Satino, Satino Satino (Jurnal Studi Keperawatan, 2025)
Background: Acute Myocardial Infarction (AMI) is the main cause of death globally, including in Indonesia. Hemodynamic monitoring by nurses is essential in the management of AMI. Apart from pharmacological therapy, post-AMI rehabilitation is important to prevent complications, by paying attention to psychological aspects with foot massage therapy the patient can relax so that the hemodynamic status is stable. Purpose: To determine the effectiveness of the effect of implementing foot massage therapy on changes in hemodynamic status in Acute Myocardial Infarction (AMI) patients in Dr. Moewardi Surakarta Hospital. Method: This research used a quantitative quasi-experimental design with a pre-test post-test with control design method. The research sample was 58 respondents divided into 2 groups randomly. Results: The results of the Paired Sample T-Test analysis showed that 28 respondents were given foot massage therapy and the hospital therapy program had an effect on the stability of the hemodynamic status of AMI patients, with a p-value of SBP 0.003, DBP 0.001, MAP 0.042, HR 0.001, and RR 0.002. Conclusion: This research shows that foot massage therapy for 15-20 minutes a day for 3 days can stabilize the hemodynamic status of AMI patients.Keyword :  hemodynamic status, foot massage therapy, acute myocardial infarction